Low Brine Shrimp Bio-Toxicity Marine Lubricating Hydraulic Fluid with Ultra-Low Friction Coefficient and Enhanced Frictional Heat Suppression - Wei Li; Huanyi Chen; Long Chen; Shanqin Ge; Qingzhao Cai; Genxiang Gong; Jinhong Yu; Kazuhito Nishimura; Nan Jiang; Tao Cai (Lubricants)
Hydraulic technology has been instrumental in the extensive application of offshore mechanical equipment, particularly in drilling platforms and ships, where high-performance hydraulic fluids are essential for safe and efficient operations. Addressing the urgent need for water-based hydraulic fluids as an alternative to traditional oil-based fluids, this study introduces a novel water-based hydraulic fluid fortified with phytic acid, derived from plant seeds, to achieve low biotoxicity, low coefficient of friction, and reduced frictional heat generation. The integration of phytic acid has significantly enhanced the lubricating performance, reducing the average coefficient of friction to as low as 0.013, as tested by the four-ball tester, which is the lowest value reported to date. Real-time monitoring of the temperature rise of the friction testing apparatus using an infrared thermal imager revealed a 78.6% reduction in temperature increase. Acute toxicity assays using Brine Shrimp demonstrated that the 96 h LC50 value for the water–glycol flame-resistant hydraulic fluid with added phytic acid exceeded 26,304 mg/L, indicating low toxicity. Characterization analyses elucidated the mechanisms underlying the improved tribological properties, highlighting the potential of this eco-friendly fluid for safe and efficient offshore operations.